Efek Dampak Kebijakan DEBT Switching Terhadap Keuangan negara - Eri Hariyanto (Magister Ilmu Administrasi Publik, 2006)
As an effect of the economic crisis in 1997-1998, the Government of Indonesia has issued 650.000 billion rupiah of government bonds to restructure banks. These bonds called recapitalization bonds. Problems surface when the maturity date of bonds is in 2004 to 2009. That will burden the state budget (APBN). To overcome that problem, the Government of Indonesia implements the Debt Switching Policy in 2002 and 2003. This article is to discuss effects of the Debt Switching Policy on the state budget (APBN) and to comprehend the economy and politic phenomenon informulating that poling.